2022
DOI: 10.21203/rs.3.rs-1394526/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pelvic packing or endovascular interventions: which should be given priority in managing hemodynamically unstable pelvic fractures? A systematic review and a meta-analysis

Abstract: Background: Pelvic fractures in trauma patients can be associated with substantial massive hemorrhage. Mainly hemostasis interventions consist of pelvic packing (PP) and endovascular intervention (EI), such as angiography-embolization (AE) and resuscitative endovascular balloon occlusion of the aorta (REBOA). Whether PP or EI should be given priority for the management of hemodynamic unstable patients with pelvic fractures is still under debate. This meta-analysis aims to find out the evidence-based recommenda… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“… 6 However, the treatment effects of using AE or EPP to control hemorrhage associated with traumatic pelvic fractures are controversial. 7 Recent studies have explored this controversy. A retrospective cohort study utilizing the American College of Surgeons Trauma Quality Improvement Program database from 2016 to 2018 showed no significant difference in in-hospital survival between the AE and preperitoneal packing groups, although preperitoneal packing was more frequently chosen for severe pelvic fractures necessitating laparotomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 However, the treatment effects of using AE or EPP to control hemorrhage associated with traumatic pelvic fractures are controversial. 7 Recent studies have explored this controversy. A retrospective cohort study utilizing the American College of Surgeons Trauma Quality Improvement Program database from 2016 to 2018 showed no significant difference in in-hospital survival between the AE and preperitoneal packing groups, although preperitoneal packing was more frequently chosen for severe pelvic fractures necessitating laparotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that EPP is a relatively simple and effective protocol for controlling pelvic hemorrhage in resource-limited scenarios. 7 Most pelvic hemorrhage originates from venous bleeding, 11 and compression packing is an effective method to stop such bleeding. As a prerequisite for EPP, the pelvic ring must remain stable to provide sufficient support for gauze packing.…”
Section: Introductionmentioning
confidence: 99%